Frequency of Cardiovascular Manifestation in Patients With Rheumatoid Arthritis - Kumar, Pardeep (Cureus, 2021)
Introduction Rheumatoid arthritis (RA) is a chronic, inflammatory, systemic autoimmune disease. The increased inflammatory burden in RA may result in atherosclerosis, myocardial infarction (MI), and subsequent mortality. In this study, we will determine the frequency of cardiovascular manifestation in RA patients through history, laboratory workup, and echocardiography. Methods This cross-sectional study was conducted in the rheumatology unit of a tertiary care hospital in Pakistan. Three hundred and twenty-two (n=322) participants with a previously confirmed diagnosis of RA were enrolled in this study via consecutive convenient non-probability sampling. Results Cardiovascular manifestations were present in 188 (58.3%) participants. More participants had positive rheumatoid factor (82.9% vs. 32.8%; p-value: < 0.0001) in RA patients with cardiovascular manifestation compared to RA patients without cardiovascular manifestation. Patients with cardiovascular manifestations have a significantly higher C-reactive protein (CRP; 10.21 ± 2.81 mg/L vs. 8.17± 2.01 mg/L; p value: < 0.0001) and erythrocyte sedimentation rate (ESR; 16.2 ± 3.14 mg/L vs. 15.1 ± 2.99 mg/L; p value: 0.0017). Conclusion In this study, patients with a cardiovascular manifestation had a higher frequency of patients with rheumatoid factor, higher mean values of CRP and ESR. The early diagnosis and management of cardiac manifestations would aid in controlling the severity of the disease and the overall mortality.